A question of balance : Charles Seeger's philosophy of music - Greer, Taylor Aitken, 1955- (University of California Press, 1998)
"For more than half a century Charles Louis Seeger (1886-1979) led a distinguished career in American music as composer, teacher, author, administrator, and humanist. Seeger's musical life was as eclectic as it was abundant: he not only championed traditions outside the mainstream, including folk and popular music, but also drew on fields outside of music, such as anthropology, linguistics, philosophy, and folklore. In A Question of Balance, Taylor Greer argues that Seeger's central contribution to the field of music was his aesthetic philosophy, which can be described as a marriage of conflicting temperaments: an artistic instinct mediated by a rational intellect."--Jacket.